Pendidikan Kesehatan Bagi Remaja Dalam Upaya Pencegahan Pelecehan Seksual Dengan Meningkatkan Kualitas Hubungan Orang Tua Dan Remaja - Kubangun, Nur Aida; Lubis, Halimahtussakdiyah; Nurlela, Lela; Lalihun, Ishak; Puspitarini, Nurul Aisyiyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Health sociology study that sexual crimes are a form of social deviation. This is because the act is very contrary to the provisions of norms and positive laws that apply to be studied from the legal aspect, causes and solutions to resolve the problem of sexual harassment socially. The purpose of the PkM activity is an effort to prevent sexual harassment of adolescents and it is expected to know the parts of the body with permissible and unacceptable touch and efforts to avoid various forms of deviation and sexual behavior. The method of PKM activities from this program is health education for adolescents in an effort to prevent sexual harassment by improving the quality of parent-adolescent relationships. The results of the activity were carried out well and smoothly with the number of participants in this activity totaling 41 people. The conclusion is that sexual violence against adolescents is a form of violence that is destructive and violates so that individual awareness and the active role of society in strengthening the mechanism for protecting adolescents from sexual violence still need to be pursued together to produce a positive and meaningful impact in protecting adolescents in their social environment.